Plasmonic Wave Validation via Finite Element Modeling and Opto-plasmonic System for Biosensor - Muhammad Rosli Abdullah; Noor Hasmiza Harun; S Noorjannah Ibrahim; Azimah Abdul Wahab; Mohd Azerulazree Jamilan (International Journal of Integrated Engineering, 2024)
Plasmonics are light and free electrons interaction in metal nanostructures. Free electrons are oscillated and known as plasmon when light hits the metal. Matched plasmon/ light at respective frequency/ momentum generates a resonance at maximum excitation of plasmonic energy. A resonance shift indicates significant molecular binding for biological matters. Plasmonic biosensors experience unpredictable outcomes without a theoretical agreement. Finite Element Modeling (FEM) could investigate effects, factors and scenarios for a real-time solution. Opto-plasmonic compares FEM to optimize parameters for generating the plasmonic energy. The objective is to perform and validate FEM with an Opto-plasmonic system according to Brewster, critical and resonance angles. A 2D geometries of BK7(1000um)- Au(50nm)- Air(1000nm) were modelled in the Electromagnetic Frequency Domain with Floquet’s periodic boundary condition. The Opto-plasmonic consists of 1- Optics (650nm laser, prism, slit, polarizer, photodiode), 2- Mechanical (Bipolar stepper motors, gears, stages) and 3- Electronics (PIC18F4550, LCD and drivers). The P-polarized beam was reflected via a prism and read by a photodiode at 0.045° and 0.1125°, respectively. Experimental to FEM accuracy indicates percentage differences for ?c, ?r, ?r, FWHM, and Rmin at 3.72%, 0.2%, 3.37%, 4.64% and 0%, respectively. Excellence validation was successfully achieved between FEM and Opto-plasmonic. In conclusion, the opto-plasmonic system can generate plasmonic energy for a biosensor application.